Identifying causation in hypersensitivity pneumonitis: a British perspective. Issue 1 (3rd December 2019) - Barber, Christopher Michael; Burge, P Sherwood; Feary, Jo R; Parfrey, Helen; Renzoni, Elizabeth A; Spencer, Lisa G; Walters, Gareth I; Wiggans, Ruth E
Abstract : Background: Establishing whether patients are exposed to a 'known cause' is a key element in both the diagnostic assessment and the subsequent management of hypersensitivity pneumonitis (HP). Objective: This study surveyed British interstitial lung disease (ILD) specialists to document current practice and opinion in relation to establishing causation in HP. Methods: British ILD consultants (pulmonologists) were invited by email to take part in a structured questionnaire survey, to provide estimates of demographic data relating to their service and to rate their level of agreement with a series of statements. A priori 'consensus agreement' was defined as at least 70% of participants replying that they 'Strongly agree' or 'Tend to agree'. Results: 54 consultants took part in the survey from 27 ILD multidisciplinary teams. Participants estimated that 20% of the patients in their ILD service have HP, and of these, a cause is identifiable in 32% of cases. For patients with confirmed HP, an estimated 40% have had a bronchoalveolar lavage for differential cell counts, and 10% a surgical biopsy. Consensus agreement was reached for 25 of 33 statements relating to causation and either the assessment of unexplained ILD or management of confirmed HP. Conclusions: This survey has demonstrated that although there is a degree of variation in the diagnostic approach for patients with suspected HP in Britain, there is consensus opinion for some key areas of practice. There are several factors in clinical practice that currently act as potential barriers to identifying the cause for British HP patients.